An analysis of the effects of a campaign supporting use of a health symbol on food sales and shopping behaviour of consumers - Trine Mørk; Klaus G. Grunert; Morten Fenger; Hans Jørn Juhl; George Tsalis (BMC, 2017)
Abstract Background Since 2009, the green Keyhole symbol has been a joint Nordic initiative for signalling healthfulness of specific food products. In 2014, the Danish Ministry of Food, Agriculture and Fisheries carried out a campaign aimed mainly at men over 35 with a low level of education, encouraging them to use the Keyhole in their shopping process. The objective of the study is to evaluate the campaign by measuring its effect on consumer behaviour in the store. Methods The impact of the Keyhole campaign was measured in selected retail stores. Sales data were analysed to ascertain whether sales of Keyhole labelled products changed during and after the campaign. Observations and interviews were conducted in the same stores. Results The campaign had a positive effect on sales of Keyhole-labelled products in two out of three retail chains investigated. In these two retail chains, sales of Keyhole labelled products rose by about 20%. In the third chain, there was a slight decrease of sales of Keyhole labelled products. The effect differed considerably between product categories. Analysis of the interview data indicated that by the end of the campaign, shoppers with a short education had a higher likelihood of mentioning health as a purchase motive, and there was a higher general tendency to look for nutrition information. Conclusions Results suggest that the campaign did have effects on shopper behaviour and that it is possible to address shoppers with a short education by a tailored campaign. However, long-term effect of the campaign was not ascertained.